2015
DOI: 10.1016/j.ijpsycho.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Integrating affective and cognitive correlates of heart rate variability: A structural equation modeling approach

Abstract: High frequency heart rate variability (HRV) is a measure of neurocardiac communication thought to reflect predominantly parasympathetic cardiac regulation. Low HRV has been associated empirically with clinical and subclinical levels of anxiety and depression and, more recently, high levels of HRV have been associated with better performance on some measures of executive functioning (EF). These findings have offered support for theories proposing HRV as an index measure of a broad, self-regulatory capacity unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 127 publications
(208 reference statements)
3
19
0
2
Order By: Relevance
“…The results parallel recent evidence suggesting low associations among selfregulation indices in general (Saunders et al, 2018) and in older adults specifically. For example, investigations of HRV and EF using MIDUS II data (a middle-age and older adult sample) reported no significant associations between multifaceted EF and HRV after accounting for age, sex, and education (Kimhy et al, 2013;Mann et al, 2015). Additionally, subjective self-regulation (assessed via the BRIEF) did not significantly correlate with standardized neuropsychological tests of EF in older adults (including processing speed, working memory, verbal fluency, setshifting, and cognitive inhibition; Meltzer et al, 2017;Rabin et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The results parallel recent evidence suggesting low associations among selfregulation indices in general (Saunders et al, 2018) and in older adults specifically. For example, investigations of HRV and EF using MIDUS II data (a middle-age and older adult sample) reported no significant associations between multifaceted EF and HRV after accounting for age, sex, and education (Kimhy et al, 2013;Mann et al, 2015). Additionally, subjective self-regulation (assessed via the BRIEF) did not significantly correlate with standardized neuropsychological tests of EF in older adults (including processing speed, working memory, verbal fluency, setshifting, and cognitive inhibition; Meltzer et al, 2017;Rabin et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…In a large sample of U.S. adults, Mann et al ( 2015 ) found a significant association between HF HRV (the only HRV measure reported) and a latent cognitive variable (including a WM test/digit backwards, a Go-NoGo task, and category fluency, often used as a semantic memory test) but no association with the latent cognitive variable after adjustments for demographical factors. However, the basic bivariate correlations reported showed that the only cognitive measure that was significantly associated with HF HRV was the Go-NoGo task which tapped the executive processes of inhibition and attentional set-shifting.…”
Section: Introductionmentioning
confidence: 99%
“…It has been amply documented that the high-frequency power of heart rate variability (HF-HRV) decreases in stress states ( Mazurak et al, 2013 ; Chalmers et al, 2014 ; Kuehl et al, 2015 ; Visnovcova et al, 2015 ). High levels of HF-HRV are linked to better performance on executive function ( Mann et al, 2015 ), which mediated the correlation between HF-HRV and cheerfulness/calmness ( Geisler et al, 2010 ). A few studies have demonstrated that relaxing music increase listeners’ HF-HRV ( Okada et al, 2009 ; Peng et al, 2009 ; Chuang et al, 2010 , 2011 ; da Silva et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%